If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(4x + -10) = 52 + 3x Reorder the terms: 0.5(-10 + 4x) = 52 + 3x (-10 * 0.5 + 4x * 0.5) = 52 + 3x (-5 + 2x) = 52 + 3x Solving -5 + 2x = 52 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -5 + 2x + -3x = 52 + 3x + -3x Combine like terms: 2x + -3x = -1x -5 + -1x = 52 + 3x + -3x Combine like terms: 3x + -3x = 0 -5 + -1x = 52 + 0 -5 + -1x = 52 Add '5' to each side of the equation. -5 + 5 + -1x = 52 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 52 + 5 -1x = 52 + 5 Combine like terms: 52 + 5 = 57 -1x = 57 Divide each side by '-1'. x = -57 Simplifying x = -57
| 69=3v | | 3x-6+x+8=42 | | 5xy^2+3xy^2= | | -5w^2+23w-42=0 | | 11=4x-3y | | 0=-16t^2+50t+6 | | 5x-4=3x+2x+3-2+1 | | 72=5c+7c-2c | | n+5=-1-16 | | 2(-3a+5)=2y+3 | | 68=4v | | a(a^7+1)-7(a^7+1)=0 | | 4x-3=x-3+3x | | 3(4)-6+4+8=42 | | m+5=1 | | 12x-7=27x+3 | | -1x=13 | | 34a-4(5d+2)=36 | | 235=177-x | | -5n-15n=10 | | 6x-2=4x-(-2x+2) | | J=9(3.14)p | | 3x-3=2x-16 | | -5n-n=10 | | 3x-2=16-x^2 | | 185-u=252 | | 3x+5+6x=15 | | 14x+7-2=7 | | 11(y-2)=13(y+4) | | 3p^2+4p=8 | | 11T=8D+12pm | | 4(x+2)+3(2x-5)=31 |